Skogsnäringens ansvarstagande för den biologiska mångfalden - Pehrsson,Victoria (2023)
Society's increased demand for wood has led to amplified extraction of forests, which has negatively affected the preservation of biological diversity. In Sweden, the world's fourth largest wood exporter, forest conservation legislation is based on freedom with responsibility, which means that forest owners are expected to take personal responsibility for the consideration of the forest's various values. Criticism on the responsibility has, however, been leveled, especially regarding the conservation of biological diversity. Therefore, this study examines how different stakeholders are taking responsibility in the forestry value chain, with a focus on the conservation of biodiversity. In addition, the study examines the stakeholder’s point of view on how to ensure the conservation of biodiversity in the future. The study was based on 20 semi-structured interviews with different stakeholders working in, with, or in connection to forestry. The results were thematized with both inductive and deductive methods. The results show that most of the responsibility lies with the forest owners, and that certifications are used to verify the responsibility. However, due to vague laws and requirements, the certifications do not ensure enough protection of the forest's biodiversity. Furthermore, the responsibility for conservation of biodiversity in the value chain is complex and faces challenges regarding economic resources, lack of measurements, and conflicts of interests. The driving force to take responsibility is based on self-interest, future generations, the market, business strategy, and the economy. The results also concluded that the future will obtain business models based on new measurements for biodiversity and regulations that the EU will create. These instruments will affect the entire value chain's responsibility, rather than just the forest, to ensure conservation of biodiversity.
Keywords: Skogsindustri; skogspolitik; skogsnäringens värdekedja; ansvarstagande; biologisk mångfald; drivkrafter; utmaningar; framtidsutsikter